1995
DOI: 10.1161/01.hyp.25.6.1270
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Cardiac Autonomic Control in Humans by Angiotensin II

Abstract: Angiotensin II (Ang II) exerts an inhibitory action on vagal activity in animals and may also facilitate sympathetic activity. The object of this study was to compare autonomic activity resulting from equivalent steady-state baroreflex activation during intravenous Ang II infusion with that resulting from a control infusion of phenylephrine. Eight healthy subjects aged 22 to 34 years were studied in a single-blind, randomized, prospective crossover study. Autonomic activity was determined by computer analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
1
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 32 publications
0
52
1
1
Order By: Relevance
“…21,[27][28][29] Many studies have demonstrated that HT volunteers exhibit a reduction in HRV that is associated with a decrease in vagal autonomic modulation and an increase in sympathetic modulation. [30][31][32] Our study demonstrated that untreated HT volunteers presented an increase in HVR that was characterized by an increase in total variance in the RRi compared with NT and HT volunteers treated with Enalapril. Although this increase appears paradoxical, it was the result of an increase in sympathetic autonomic modulation because the LF oscillations in these volunteers were notably high.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…21,[27][28][29] Many studies have demonstrated that HT volunteers exhibit a reduction in HRV that is associated with a decrease in vagal autonomic modulation and an increase in sympathetic modulation. [30][31][32] Our study demonstrated that untreated HT volunteers presented an increase in HVR that was characterized by an increase in total variance in the RRi compared with NT and HT volunteers treated with Enalapril. Although this increase appears paradoxical, it was the result of an increase in sympathetic autonomic modulation because the LF oscillations in these volunteers were notably high.…”
Section: Discussionmentioning
confidence: 57%
“…Indeed, ACEis and AT1 receptor antagonists promote an improvement in autonomic function in different contexts, including baroreflex sensitivity evaluation and HRV analysis. 11,28,30,36,37 The mechanisms that underlie ACEi improvement of HRV modulation have not been elucidated, but ACEis and/or AT1-receptor antagonists primarily affect neural sites that are involved in the cardiovascular regulation, such as the solitary tract nucleus, rostral ventrolateral medulla, paraventricular nucleus and area postrema. However, the identification of the exact mechanism of action has been hindered by the complex interaction of the sites involved in cardiovascular control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Both sympathetic tone and cardiac vagal activity are known to be favourably modified by the reduction of circulating angiotensin II. 43,44 In the ramipril-treated aortic banded rats, regression of compensatory hypertrophy was also paralleled by improved survival: 31% died in the placebo treated group during 12 weeks follow-up compared with 11% in the ramipril-treated group. 37 …”
Section: Increased Survivalmentioning
confidence: 91%
“…HF is characterized by altered neural cardiovascular regulation, including increased resting sympathetic nerve activity to the heart and vasculature, depressed vagal outflow to the heart, and attenuated baroreflex control of HR (6,31,33,36,37). Recently, Iellamo et al (14) found that the spontaneous baroreflex control of HR in HF subjects was significantly depressed compared with normal subjects.…”
Section: Cardiac Baroreflex Responses In Hfmentioning
confidence: 99%